2021
DOI: 10.5055/jem.0591
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for the disaster workforce during a compound hurricane–pandemic

Abstract: The COVID-19 pandemic has created new workforce considerations for emergency management community in addressing cumulative and cascading disasters. This research identifies how emergency management planning for both the changing dynamics of COVID-19 and the upcoming hurricane season may change under a compound threat. Many jurisdictions have faced challenges in providing adequate staffing of shelters before the pandemic. Now, fatigue among staff further exacerbates these challenges as resources are stretched t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Risk varies for organizations and communities based on both socio-economic conditions and the hazardousness of the location in which they operate (Blaikie et al 2014). Marshall et al (2021) found that emergency shelter providers from all sectors reported workforce and budget strains resulting from the pandemic. Volunteers and funding decrease while operating costs and staffing needs from implementing distancing protocols and securing personal protective equipment (PPE) increase (Rao and Greve 2018).…”
Section: Shelter Resilience To the Covid-19 Pandemic And The Resultin...mentioning
confidence: 99%
See 4 more Smart Citations
“…Risk varies for organizations and communities based on both socio-economic conditions and the hazardousness of the location in which they operate (Blaikie et al 2014). Marshall et al (2021) found that emergency shelter providers from all sectors reported workforce and budget strains resulting from the pandemic. Volunteers and funding decrease while operating costs and staffing needs from implementing distancing protocols and securing personal protective equipment (PPE) increase (Rao and Greve 2018).…”
Section: Shelter Resilience To the Covid-19 Pandemic And The Resultin...mentioning
confidence: 99%
“…Volunteers and funding decrease while operating costs and staffing needs from implementing distancing protocols and securing personal protective equipment (PPE) increase (Rao and Greve 2018). These staffing and funding challenges threaten operational capacity and have the potential to reduce shelter utilization, thereby placing vulnerable populations at heightened risk (AbouAssi et al 2019; Maher, Hoang, and Hindery 2020; Marshall et al 2021; Whytlaw et al 2021).…”
Section: Shelter Resilience To the Covid-19 Pandemic And The Resultin...mentioning
confidence: 99%
See 3 more Smart Citations